Dropwise condensation: From fundamentals of wetting, nucleation, and droplet mobility to performance improvement by advanced functional surfaces - Zheng, Shao-Fei; Gross, Ulrich; Wang, Xiao-Dong (Advances in colloid and interface science, 2021)
As a ubiquitous vapor-liquid phase-change process, dropwise condensation has attracted tremendous research attention owing to its remarkable efficiency of energy transfer and transformative industrial potential. In recent years, advanced functional surfaces, profiting from great progress in modifying micro/nanoscale features and surface chemistry on surfaces, have led to exciting advances in both heat transfer enhancement and fundamental understanding of dropwise condensation. In this review, we discuss the development of some key components for achieving performance improvement of dropwise condensation, including surface wettability, nucleation, droplet mobility, and growth, and discuss how they can be elaborately controlled as desired using surface design. We also present an overview of dropwise condensation heat transfer enhancement on advanced functional surfaces along with the underlying mechanisms, such as jumping condensation on nanostructured superhydrophobic surfaces, and new condensation characteristics (e.g., Laplace pressure-driven droplet motion, hierarchical condensation, and sucking flow condensation) on hierarchically structured surfaces. Finally, the durability, cost, and scalability of specific functional surfaces are focused on for future industrial applications. The existing challenges, alternative strategies, as well as future perspectives, are essential in the fundamental and applied aspects for the practical implementation of dropwise condensation. [Display omitted] •Progress of dropwise condensation (DWC) on advanced functional surfaces.•Key components for the performance enhancement of dropwise condensation.•Overview of fundamental understanding and heat transfer enhancement.•Challenges and future prospects in the practical application of dropwise condensation.